Investigating the Effects of Weather on Traffic Volume and Speed at the Intra-Urban Expressways - Syed Abbas, Syed Khairi; Nur Izzah Farzana Kamarulzaman,; Jezan Md Diah,; Muhammad Akram Adnan,; Adi Yazid Rosli, (Recent Trends in Civil Engineering and Built Environment, 2025)
This study analyzes the relationship between vehicle speed and traffic volume on Malaysia's urban expressways under varying weather conditions, particularly focusing on the effects of adverse weather on driving behavior and traffic dynamics. Using advanced radar technology, specifically the SpeedLane™ Pro Counter Classifier, traffic data was collected on the Intra-Urban Expressway in Klang Valley. The data, which includes real-time and historical information on speed, volume, and weather conditions, was compared between dry and rainy days. The findings revealed a significant correlation between adverse weather conditions. They reduced traffic volume and vehicle speed, emphasizing the impact of Malaysia's tropical monsoon seasons on driving behavior and road safety. The study concludes that such weather conditions pose a safety risk to road users, highlighting the need for strategies to mitigate these effects. It recommends further research to assess the broader impact of adverse weather on road safety. It suggests continuously using advanced traffic monitoring technologies to improve traffic management under varying weather conditions.